CITRA MEREK, KEPERCAYAAN MEREK DALAM MEWUJUDKAN LOYALITAS MEREK PRODUK AQUA - Sakinah, Nurul Laela; Suhardi, Dadang (Indonesian Journal of Strategic Management, 2018)
This research aims to find out the brand image and brand trust towards brand loyalty of AQUA product. The population of this research is the consumer of AQUA in Kuningan district and the data are collected by questionnaire technique. The    purposive sampling technique is applied in this research while the sample of this research is 100 respondents using measurement scale of interval scale. The analysis method in this research is descriptive and verification with quantitative approach that cover validity and reliability, classic assumption test, hypothesis testing through F test, T test and determination coefficient (R2). The technique of data analysis is gained by the use of multiple regression linear. All tests on this research use a measured instrument in the form of computer program SPSS (Statistical Package for the Social Science) version 21.0. Based on the result of this research, it is concluded that the brand image has positive influence and significant towards  brand loyalty ; brand trust has positive influence and significant towards  brand loyalty as well as both of brand image and brand trust have also positive influence and significant towards brand loyalty. Keywords: Brand Image, Brand Trust, Brand Loyalty